IMPLEMENTASI KARAKTER RELIGIUS DAN TANGGUNG JAWAB MELALUI PROGRAM EKSTRAKURIKULER - Shobichatul Muniroh; Mohammad Maulana Nur Kholis (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
This research aims to analyze the implementation of religious character and responsibility formed through extracurricular activities at Madrasah Tsanawiyah PP. Amanatul Ummah. This research is based on the decline in national character, because education is unable to make people spiritually, socially and intellectually intelligent. This research method uses a qualitative research type with a case study approach, observation, interview and documentation data collection methods. Data sources in the research include student affairs, extracurricular supervisors, accompanying teachers and students. The results of this research show that there are four extracurriculars that can shape religious character and responsibility, including: scouting, archery, banjari and tahfidz extracurriculars. Religious character is proven by the habit of praying before and after every exercise, polite attitude, and the habit of admirable morals. Meanwhile, the character of responsibility is proven by the students' responsibility to train and lead their younger classmates, their responsibility to seriously carry out the exercises, and is responsible for safeguarding the memorized Al-Quran.